Psychosocial Support for Enhancing the Well-Being of Chronic Kidney Disease (CKD) Patients - Amir Abbas; Farman Ali (Indus Journal of Bioscience Research, 2023)
Chronic Kidney Disease (CKD) is a global public health concern with a substantial impact on individuals’ physical and psychosocial well-being. While medical interventions have made significant strides in managing CKD, the psychosocial aspect of the disease remains under-addressed. This paper aims to explore the critical role of psychosocial support in enhancing the well-being of CKD patients. We will delve into the psychosocial challenges faced by CKD patients, the benefits of psychosocial support, and various interventions and strategies that can be employed to provide holistic care for CKD patients. By focusing on the psychosocial dimension of CKD care, healthcare providers, policymakers, and researchers can contribute to improving the overall quality of life for CKD patients.